The EFFECT OF NURSING HEALTH EDUCATION INTERVENTION ON WOMEN’S KNOWLEDGE ABOUT CERVICAL CANCER IN EKITI STATE - Maitanmi, Julius Olatade; Kio, Janet Omolara; Maitanmi, Bukola Titilope; Ogungbesan, Joshua Olufemi; Atekoja , Oluwabusolami Esther (Student's Journal of Health Research Africa, 2023)
Introduction: Cervical cancer remains one of the leading causes of cancer contributing to high mortality and morbidity. Early diagnosis with screening has been linked with good prognosis but it remains a problem when the women are not aware of this screening process. Hence, the need to create awareness about cervical cancer and the screening process among women of reproductive age in Ekiti state Nigeria. Methods: One group pre-test post-test quasi-experimental research design was adopted in assessing the level of women with cervical cancer in Ekiti State. A purposive sampling technique was used in recruiting participants for the study. The same self-structured questionnaire was used to collect data at the pre and post phase. Data were analyzed using SPSS version 23. Results were presented on tables and figures showing the knowledge level before and after the nursing health education intervention. Results: The majority (38.7%) of the participants were between 41-50 years, were Christians (85.6%), Yorubas (80.8%), and were married (72.5%). Almost all (98.5%) of the participants have heard about Pap smear before but the pre-intervention knowledge about cervical cancer was low (4.86+1.70) while there was an improvement in the post-intervention phase (8.53+2.40). Conclusion: The study concluded that nursing intervention (educational package) had a positive effect on the knowledge of women of reproductive age in Ekiti state about cervical cancer screening. Recommendation: Sustained health education by health workers (nurses and others) about cervical cancer screening is strongly recommended by the researchers.